A releitura da nacionalidade para efetivação do direito social à saúde: o exemplo privilegiado do caso fronteiriço - Grellmann, Liliane Nathalie Fretes Garcia (Universidade do Vale do Rio dos Sinos, 2011)
Being the right to health a fundamental right isn’t conceivable not to implement it based on nationalities. The inevitable globalization has brought changes, influencing even the integration among countries and allowing the spread of diseases because of the easy transit, therefore, the protection and achievement of the right to health is priceless. In the present study the social right to health will be examined, from the perspective of the formal definition of fundamental rights brought by Luigi Ferrajoli. It also presents the right to health as being fundamental and a human right. Not possible to be denied because its ownership doesn’t depend on nationality or citizenship, but only on the fact of being a person. Still, the right to health from a perspective of valuation of fundamental rights will be discussed, with the introduction of these rights at the Constitutions, and from the perspective of integration and globalization in which state sovereignty and citizenship undergo significant changes. The present will provide the prime frontier example, where foreigners, in need, come to Brazil intending to use their fundamental right to health in the Brazilian health system, analyzing the right to health as a fundamental right, defending, this way, rereading the nationality for the achievement of the right to health.
Keywords: Direito à saúde; Direitos fundamentais; Releitura da nacionalidade; Right to health; Fundamental rights; Rereading nationality; ACCNPQ::Ciências Sociais Aplicadas::Direito